Molecular and cellular neuroinflammatory status of mouse brain after systemic lipopolysaccharide challenge: importance of CCR2/CCL2 signaling - Cazareth, Julie (J Neuroinflammation, 2014)
BACKGROUND: Genetic and environmental factors are critical elements influencing the etiology of major depression. It is now accepted that neuroinflammatory processes play a major role in neuropsychological disorders. Neuroinflammation results from the dysregulation of the synthesis and/or release of pro- and anti-inflammatory cytokines with central or peripheral origin after various insults. Systemic bacterial lipopolysaccharide (LPS) challenge is commonly used to study inflammation-induced depressive-like behaviors in rodents. In the present study, we investigated immune-to-brain communication in mice by examining the effects of peripheral LPS injection on neuroinflammation encompassing cytokine and chemokine production, microglia and central nervous system (CNS)-associated phagocyte activation, immune cell infiltration and serotonergic neuronal function. METHODS: LPS was administered to C57BL/6 J mice by intraperitoneal injection; brains were collected and pro-inflammatory cytokine mRNA and proteins were measured. To examine the relative contribution of the different populations of brain immune cells to the occurrence of neuroinflammation after acute systemic inflammation, we precisely characterized them by flow cytometry, studied changes in their proportions and level of activation, and measured the amount of cytokines they released by Cytometric Bead Array™ after cell sorting and ex vivo culture. Because of the central role that the chemokine CCL2 seems to play in our paradigm, we studied the effect of CCL2 on the activity of serotonergic neurons of the raphe nucleus using electrophysiological recordings. RESULTS: We report that systemic LPS administration in mice caused a marked increase in pro-inflammatory IL-1β, IL-6, TNFα and CCL2 (monocyte chemoattractant protein-1) mRNA and protein levels in the brain. Moreover, we found that LPS caused microglia and CNS-associated phagocyte activation characterized by upregulation of CCR2, TLR4/CD14, CD80 and IL-4Rα, associated with overproduction of pro-inflammatory cytokines and chemokines, especially CCL2. LPS also induced a marked and selective increase of CCR2(+) inflammatory monocytes within the brain. Finally, we showed that CCL2 hyperpolarized serotonergic raphe neurons in mouse midbrain slices, thus probably reducing the serotonin tone in projection areas. CONCLUSION: Together, we provide a detailed characterization of the molecular and cellular players involved in the establishment of neuroinflammation after systemic injection of LPS. This highlights the importance of the CCL2/CCR2 signaling and suggests a possible link with depressive disorders.